Developing Medical Technologies for Low-Resource Settings: Lessons From a Wireless Wearable Vital Signs Monitor–neoGuard - Nantume, Assumpta; Shah, Sona; Cauvel, Teresa; Tomback, Matthew; Kilpatrick, Ryan; Afzal, Bushra; Kiwanuka, Noah (Frontiers in Digital Health, 2021)
In the aftermath of the COVID-19 pandemic, digital health products have gained increasingly wide appeal for the delivery of health services to patients in high-income and low-income settings alike. As researchers, clinicians and policy makers rallied to optimize patient care and alleviate the burden on health facilities and hospital staff at the height of the pandemic, global efforts to leverage digital health solutions became more invigorated than ever before. Yet despite the recent uptick in digital health interest, innovators still struggle to navigate the existing ecosystem and face significant barriers to transitioning their ideas from concept to market, particularly in low-and-middle-income countries (LMICs) where the health technology space is maturing at a slower pace. At the same time, there is a tremendous opportunity for innovators worldwide to seize this unprecedented moment and capitalize on these recent digital health gains. In this perspective piece, the team behind the wireless vital signs monitor, neoGuard, reflects on its journey creating and commercializing a health technology product for patients in low-resource settings. By examining our own experience, we aim to offer some useful insights on potential pitfalls in medical device innovation and how to successfully navigate the current digital health ecosystem.